Preoperative Counseling Status of the Patient Undergoing Orthopedic Surgical Procedures at a Tertiary Care Center: A Descriptive Observational Study - Kunwar, Meena; Regmi, Subhash; Joshi, Amit; Bhatta, Deepa (Nepal Orthopaedic Association Journal, 2024)
Introduction: Informed written consent acts as a legal and ethical document of proof of adequate pre-operative counseling and demands the effective participation of both surgeons and patients. However, studies suggest that there is inadequacy and lack of compliance while obtaining informed consent. This results in poor patient participation and ultimately affects the doctor-patient relationship. Hence, this study was conducted to assess the counseling status of patients undergoing surgeries in a tertiary care center in Nepal. Methods: A hospital-based descriptive observational study was conducted at B & B Hospital, Gwarko, Lalitpur, Nepal, between December 1, 2023, and December 30, 2023. All patients who underwent orthopedic surgeries during the study period were included. Those who refused to take part in the study were excluded. A convenient sampling method was used. Data were obtained through interviews with selected patients. A structured questionnaire administered via Google form, was utilized for this purpose. The questionnaire included general questions related to the experience of pre-operative counseling. Descriptive statistics were used. Continuous data were reported as mean ± standard deviation and categorical data was reported as number (percentage). Results: The study had a total of 100 respondents, with a mean age of 38.38 ±15.56 years. 65 (65%) were males and 35 (35%) were females. Out of 100, 95(95%) received pre-operative counseling. 19 (19%) did not receive counseling regarding anesthesia, and 99 (99%) did not sign the consent form by themselves. Conclusion: Most patients received pre-operative counseling. However, they were not adequately informed regarding anesthesia. In addition, a large number of patients did not sign the consent form by themselves.